Teachers' self-reported beliefs on developmentally appropriate and inappropriate practices in grade K-4 EFL classrooms. Issue 4 (4th July 2017) - Mede, Enisa
ABSTRACT: This study investigated the perceived beliefs and reported practices of fourth-grade English teachers in primary (elementary) public schools in Turkey. Significantly, it aimed to examine the participating K-4 English as a foreign language (EFL) teachers' beliefs about the developmentally appropriate and inappropriate practices, discover the possible factors that might influence the planning and implementation of those instructional activities, and lastly, find out whether there is any correlation between the self-reported beliefs and practices. A sample of 158 EFL teachers teaching fourth-grade classes at Turkish public schools (primary level) participated in the study. Data were gathered from the Teacher Beliefs and Practices Survey: 3–5 Year Olds based on 1997 National Association for Education of Young Children's Developmentally Appropriate Practice (DAP) guidelines and focus group interviews. The findings revealed that future teacher training programmes should promote DAPs and enhance teachers' skills to implement them effectively in the young learners' language classrooms.